Physical And Chemical Characteristics Of Cassava Leaf Chlorophyll As Natural Dye Powder (Manihot esculenta Cranzt) With Tween 80 And Alkaline Type Variations - Winda Amilia; Andi Eko Wiyono; Retha Talia Shasabilah; Miftahul Choiron; Maria Belgis (Food, Agriculture and Natural Resources - NETWORKS, 2023)
Cassava leaves are a good source of minerals Ca, Mg, Fe, Mn, Zn, vitamins A and B2 (riboflavin). In addition, cassava leaves contain bioactive compounds that are beneficial to the body, namely chlorophyll. Chlorophyll is a natural green dye that is generally found in plants whose composition is contained in the chloroplasts. The amount of chlorophyll in cassava leaves is classified as good, namely 18.141 mg/l. This is one of the potentials to utilize cassava leaves as natural dyes. Production of cassava leaf coloring powder using foam mat drying. Foam mat drying is a method of foaming technique by adding foam. The foaming agent used is tween 80 which can produce foam or froth and speed up drying. Chlorophyll can be easily degraded due to exposure to heat (temperature), acids, light and alcohol. The use of NaHCO3 can increase the levels of chlorophyll in the leaves. In addition, the use of MgCO3 can maintain the green color of leaf chlorophyll. The purpose of this study was to determine the interaction of tween 80 variations and types of bases on the physical and chemical profiles of cassava leaf natural dye powder. The research design used a laboratory experimental method with two variations, namely tween 80 and base type. In this study there were four treatment combinations. This study used several test parameters including physical and chemical tests, namely dissolving time, color (L, a, b), total dissolved solids, pH, water content, and chlorophyll content. The results showed that the variation of tween 80, the type of base and the interaction of the two had a significant effect on the b color value and the L color value in cassava leaf natural dye powder.